Agricultural Distortions, Poverty, and Inequality in South Africa - Hérault, Nicolas; Thurlow, James (World Bank, Washington, DC, 2017)
South Africa has rapidly reduced trade barriers since the end of Apartheid, yet agricultural production and exports have remained sluggish. Also, poverty and unemployment have risen and become increasingly concentrated in rural areas. This paper examines the extent to which remaining price distortions, both domestic and foreign, are contributing to the underperformance of the agricultural sector vis-a-vis the rest of the economy. The author draws on a computable general equilibrium (CGE) and micro-simulation model of South Africa that is linked to the results of a global trade model. This framework is used to examine the effects of eliminating global and domestic price distortions. Model results indicate that South Africa's agricultural sector currently benefits from global price distortions, and that removing these will create more jobs for lower-skilled workers, thereby reducing income inequality and poverty. The author also fined that South Africa's own policies are biased against agriculture and that removing domestic distortions will raise agricultural production. Job losses in nonagricultural sectors will be outweighed by job creation in agriculture, such that overall employment rises and poverty falls. Overall, the findings suggest that South Africa's own policies are more damaging to its welfare, poverty and inequality than distortionary policies in the rest of the world. Existing national price distortions may thus explain some of the poor performance of South Africa's agricultural sector and rural development.